Analisis Retorika Persuasif Aristoteles pada Konten “Borong Bitcoin” di Channel YouTube Timothy Ronald dalam Mempersuasi Publik - Ridho Haidar Rafif; Yudiana Indriastuti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The digital asset Bitcoin, based on Blockchain technology, has gained substantial attention, especially among Generation Z and Millennials, as it stands as one of the assets within the Cryptocurrency market. Cryptocurrency focused content on YouTube has played a significant role in Bitcoin's popularity, with Timothy Ronald’s series, “Borong Bitcoin”, emerging as one of the most watched crypto contents on YouTube in Indonesia. This content's appeal lies in Timothy Ronald’s persuasive communication strategies surrounding Bitcoin and the Cryptocurrency market, earning him credibility in conveying messages effectively to the public. This study examines the persuasive rhetorical analysis of Timothy Ronald’s “Borong Bitcoin” series in influencing the audience, grounded in Aristotle's theory of persuasive rhetoric, which comprises Ethos, Pathos, and Logos. Using a qualitative descriptive research approach, this study seeks to elucidate how Aristotelian persuasive rhetoric manifests in the Borong Bitcoin content on Timothy Ronald’s YouTube channel. Content Analysis is employed as the data analysis technique, with findings demonstrating the presence of all three Aristotelian rhetorical elements Ethos, Pathos, and Logos across episodes 1 until 10 of “Borong Bitcoin” content. Future research on persuasive rhetoric is advised to broaden its scope to include various content with rhetorical elements. Additionally, studies incorporating a more diverse audience sample may provide deeper insights into specific rhetorical elements, and further exploration of visual communication could enhance the effectiveness of Ethos, Pathos, and Logos in digital content.